ISO 9001:2015 for Everyday Operations All Facts - Short, Concise and Understandable - Hinsch, Martin; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2019)
Martin Hinsch summarizes all chapters of the ISO 9001:2015 shortly. The text offers both beginners and users with little knowledge of the standard an introduction to or a refresher course on the world's most important standard for management systems. Therefore, each individual chapter of the standard is described. The text is primarily aimed at those QM enthusiasts who would like to gain a basic understanding of the standard briefly, concisely and precisely about all the requirements relevant for day-to-day operations. Contents Basics, Structure and Key Characteristics The Certification Process Brief Description and Explanation of all ISO 9001 Chapters Target Groups Newcomers to ISO 9001:2015 with practical experience About the Author Prof. Dr. Martin Hinsch is an expert in aeronautical quality and process management. He is approved as an auditor for ISO 9001:2015 and for the aviation standard EN 9100. With his management consultancy he supports companies in setting up QM systems.
Basics, Structure and Key Characteristics -- The Certification Process -- Brief Description and Explanation of all ISO 9001 Chapters.
Keywords: Security systems; Industrial Management; Aerospace engineering; Astronautics; Security Science and Technology; Industrial Management; Aerospace Technology and Astronautics